Die Erfahrung von Armut Eine Analyse der Lebenswelt von Personen in Mangel- und Ausschlusslagen in Großbritannien - Erhard, Franz (Verlag Barbara Budrich, 2021)
The book examines poverty on the basis of qualitative interviews and makes clear that the term conceals an entire lifeworld. Great Britain as the area of study is seen as the prototype of a 'neoliberal' welfare state in which poverty leads to the devaluation of social status. This is differentiated on the basis of the experiential dimensions of time, space and sociality. Social work helps those affected to counter the devaluations.